Jean-Jaques Rousseau dalam Demokrasi - Wijaya, Daya Negri (Political Science Program, Universitas Negeri Semarang, 2016)
JJ Rousseau is one of political thinkers. He lives in the advance of science and art. However, he realizes that the progress of science and art declines the moral of society. Democracy, in his view, should be implemented by direct rule without any representation. This is caused by the freedom of every citizens which should be struggled. Everyone has a natural right which could not be seized and be given for others. They make a social contract to shape a nation. A government is developed which is not to limit a power but to ensure the freedom of a power. In addition, he gives an idea on how to build a democratic society. This article is expected to give a moral guidance for politicians.